A Trampoline Group: Feasibility, Implementation, and Outcomes - S.A. Schoen; C. Einck; A. Valdez; V. Spielmann; L.J. Miller (Moscow State University of Psychology and Education, 2019)
This paper reflects two studies designed to explore feasibility and outcomes of a movement-based trampoline group for children with autism and/or sensory processing challenges. A pre experimental A- B single subject pilot study was used to examine feasibility and sensitivity of outcomes, followed by a single group pretest posttest design to examine outcomes. Each group received eight to ten, 50-minute sessions of trampoline activity. Motor outcomes were administered once a week as well as pre- post- measures of motor function. Measures from Study 1 informed Study 2. Parent report pre- post- measures of social functioning were added to Study 2. All procedures were feasible and sensitive outcome measures were identified. In Study 1, outcomes (e.g. broad jump, heel toe walking, beads in box, beads on rod and hand strength) did not consistently show change. Broad jump and one foot standing balance were suggested for future use. In Study 2 significant improvements were noted in broad jump. Social competency and participation as measured by the Social Skills Improvement System, and the Sensory Processing Three Dimensions Occupational Performance Scale showed significant change. A visual analog scale completed by parents was also sensitive to changes in both motor and social abilities. This study demonstrated the feasibility of conducting a trampoline group program for children with autism and/or sensory processing challenges. Motor gains were reported as well as gains in psychosocial functioning.